The implementation of collection development in the Gempita Pustaka School Library - Putra, Diaz Lana; Putri, Yasmin Ananda; Sofiyani, Zulfatun (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. School libraries serve as educational resources; nevertheless, the collection development process is commonly ignored or executed improperly. The objective of the study is to examine the Gempita Pustaka Library’s collection development process and strategic position by implementing Evans & Saponaro collection development method and SWOT analysis. Research method. The study was performed through descriptive qualitative method, incorporating observations and conducting interviews in collecting data. Data analysis. Data analysis was conducted using the collection development process by Evans and Saponaro, while SWOT analysis was applied to identify internal analysis (strengths and vulnerabilities). Subsequently, an external analysis was conducted to investigate opportunities and threats, to identify strategic areas of focus. Results and Discussion. Evans and Saponaro outline six essential phases for collection development. However, the collection development process at the Gempita Pustaka Library demonstrates certain weaknesses, particularly due to the absence of regular evaluations. This issue is of a significant concern. Consequently, strategic planning was utilized to leverage the library's strengths and enhance the processes. Conclusion. The findings indicate that the Gempita Pustaka Library's six-stage collection development approach has effectively been implemented. Therefore, the study serves as a reference for improving school library collection development process in the future.